Synergistic in vitro activity and mechanism of KBN lotion and miconazole nitrate against drug-resistant Candida albicans biofilms - Cao, Xiaoyu; Xiao, Ni; Huang, Jingyi; Li, Li; Zhong, Lian; Zhang, Jun; Wang, Fengyun (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundIn the face of increasing antifungal resistance among Candida albicans biofilms, this study explores the efficacy of a combined treatment using Kangbainian lotion (KBN) and miconazole nitrate (MN) to address this challenge.MethodsUsing UPLC-Q-TOF/MS Analysis for Identification of Active Compounds in KBN Lotion; FICI for synergy evaluation, XTT and ROS assays for biofilm viability and oxidative stress, fluorescence and confocal laser scanning microscopy (CLSM) for structural and viability analysis, and real-time fluorescence for gene expression.ConclusionOur study indicates that the combined application of KBN and MN somewhat impacts the structural integrity of Candida albicans biofilms and affects the expression of several key genes involved in biofilm formation, including ALS1, ALS3, HWP1, HSP90, and CSH1. These preliminary findings suggest that there may be a synergistic effect between KBN and MN, potentially influencing not only the structural aspects of fungal biofilms but also involving the modulation of genetic pathways during their formation.